Equilibrium unfolding of the PDZ domain of β2-syntrophin - Torchio, Gabriela María (2012)
β2-syntrophin, a dystrophin-associated protein, plays a pivotal role in insulin secretion by pancreatic β-cells. It contains a PDZ domain (β2S-PDZ) that, in complex with protein-tyrosine phosphatase ICA512, anchors the dense insulin granules to actin filaments. The phosphorylation state of β2-syntrophin allosterically regulates the affinity of β2S-PDZ for ICA512, and the disruption of the complex triggers the mobilization of the insulin granule stores. Here, we investigate the thermal unfolding of β2S-PDZ at different pH and urea concentrations. Our results indicate that, unlike other PDZ domains, β2S-PDZ is marginally stable. Thermal denaturation experiments show broad transitions and cold denaturation, and a two-state model fit reveals a significant unfolded fraction under physiological conditions. Furthermore, Tm and Tmax denaturant-dependent shifts and noncoincidence of melting curves monitored at different wavelengths suggest that two-state and three-state models fail to explain the equilibrium data properly and are in better agreement with a downhill scenario. Its higher stability at pH > 9 and the results of molecular dynamics simulations indicate that this behavior of β2S-PDZ might be related to its charge distribution. All together, our results suggest a link between the conformational plasticity of the native ensemble of this PDZ domain and the regulation of insulin secretion.